2018
DOI: 10.1016/j.jval.2018.09.1802
|View full text |Cite
|
Sign up to set email alerts
|

Pms88 - Real World Persistence and Adherence With Oral Bisphosphonates for Osteoporosis - A Systematic Review

Abstract: disagree and 7¼completely agree). Consensus was established when at least 75% of the respondents reached agreement (5-7 points) or disagreement (1-3 points). Descriptive statistics were applied. RESULTS: One hundred and fifteen panelists completed the questionnaire (rheumatologists: 75.7%; dermatologists: 15.7%; nurses 1.7%; hospital pharmacists: 2.6%; clinical psychologists: 1.7%; and healthcare managers: 2.6%). In PsA patients with peripheral involvement, consensus was reached on the use of either Disease Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Bisphosphonates were shown to effectively reduce periprosthetic bone resorption and improve the longterm duration of knee prosthesis [7]. Guidance from the UK National Institute for Health and Care Excellence (NICE) recommends alendronate as the first choice of OP treatment [8], and oral administration is the most commonly used way for using bisphosphonates to treat osteoporosis [9]. It has been reported that oral alendronate not only prevented osteoclast-mediated bone loss and associated implant loosening in total hip arthroplasty (THA) [10], but also significantly reduced early postoperative periprosthetic bone loss in TKA patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Bisphosphonates were shown to effectively reduce periprosthetic bone resorption and improve the longterm duration of knee prosthesis [7]. Guidance from the UK National Institute for Health and Care Excellence (NICE) recommends alendronate as the first choice of OP treatment [8], and oral administration is the most commonly used way for using bisphosphonates to treat osteoporosis [9]. It has been reported that oral alendronate not only prevented osteoclast-mediated bone loss and associated implant loosening in total hip arthroplasty (THA) [10], but also significantly reduced early postoperative periprosthetic bone loss in TKA patients [11].…”
Section: Introductionmentioning
confidence: 99%